Divided we stand the strategy and psychology of Ireland's dissident terrorists - Horgan, John, 1974- (Oxford : Oxford University Press, 2013)
Drawing on one of the largest open-source militant databases yet assembled, this book describes the activities, histories, motivations, psychology, and strategy of the small, dynamic, and rapidly evolving splinter groups that continue to erode peace, stability, and normalization in Northern Ireland.
Description based on online resource; title from home page (viewed on Jan. 3, 2013).
Includes bibliographical references and index.
Keywords: Terrorism -- Northern Ireland; Irish Republican Army; Irish unification question; Northern Ireland -- Politics and government -- 1994-